PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA GURU SMA NEGERI 1 AMPANA - Hasan, Djufri (Katalogis, 2017)
The research intends to explore and analyze simultaneous influence of principal’s leadership and physical work environment on the performance of teachers in SMA 1 of Ampana; to explore and analyze the influence of principal’s leadership on the performance of teachers in SMA 1 of Ampana; to explore and analyze the influence of physical work environment on the performance of teachers in SMA 1 of Ampana. The research is explanative that shows the relations of variables by selecting 35 respondents with census method. Based on multiple linear regressions analysis, it is found that principal’s leadership and physical work environment simultaneously have positive and significant influence on the performance of teachers in SMA 1 of Ampana; principal’s leadership positively and significantly influence the performance of teachers in SMA 1 of Ampana; physical work environment positively and significantly influence the performance of teachers in SMA 1 of Ampana.